Decomposição assistida por radiação micro-ondas e ultravioleta de resíduos de equipamentos elétricos e eletrônicos para determinação de Br, Cd, Cr, Hg, Pb e Sb - Iop, Gabrielle Dineck (2017)
In this work, a method for ultraviolet and microwave-assisted wet digestion (MAWD-UV) was developed for digestion of waste electrical and electronic equipment (WEEE) for further determination of Br, Cd, Cr, Hg, Pb and Sb by inductively coupled plasma mass spectrometry (ICP-MS). The polymeric portion of a keyboard for desktop computer was used as a sample model for method optimization. Reference values were obtained using microwave-assisted wet digestion (MAWD) and microwave- induced combustion (MIC) methods from literature, as well as neutron activation analysis (NAA). Accuracy of MAWD-UV was investigated by spike recovery experiments and digestion of certified reference materials (CRMs). Digestion efficiency of MAWD-UV was evaluated by the determination of carbon content and residual acidity in digests and it was compared with that obtained by MAWD, using 1 to 14 mol L-1 HNO3 solutions. It was possible to observe an improvement on the digestion efficiency by using the UV lamps for more diluted solutions. The main parameters of MAWD-UV were investigated, as the digestion solution (HNO3 solutions, HNO3 and HCl solutions, addition of H2O2 or alkaline solutions), the atmosphere on the digestion vessel (5 or 10 bar of O2), and the irradiation program (power and time). Quantitative recoveries for bromine and metals were obtained using a mixture containing 0.5 mol L-1 HNO3, 0.5 mol L-1 HCl, with 5.3 mol L-1 H2O2, with a 60 min total digestion time (including cooling). With regard to the accuracy, the results obtained for digestion of CRMs of low density polyethylene (EC680k and EC681k) using MAWD-UV presented no statistical difference in comparison to the certified values, except for chromium. Limits of quantification from 0.010 μg g-1 (Cd) to 4.5 μg g-1 (Br) were obtained, in agreement to the legislation requirements. The MAWD-UV method allowed the determination of bromine and metals using a single sample preparation method, with diluted acids, suitable digestion efficiency and no bromine losses.